(untitled) (Al-Aasar, 2025)
Religion has remained a central phenomenon in human history, influencing moral values, social structures, and intellectual traditions across civilizations. This study examines the concept of religion by exploring its linguistic roots, technical definitions, and historical development, with particular emphasis on the distinction between the commonly used term “religion” and the Islamic concept of Dīn. The research analyzes the usage and applications of the term Dīn in the Qur’an, demonstrating its comprehensive scope encompassing belief, law, morality, and a complete way of life. Furthermore, the study critically evaluates Western intellectual interpretations of religion, including evolutionary theories that perceive religion as a product of social and psychological development. The views of prominent thinkers such as Professor Lutfi Levonian, Rashid Ahmad, Ali Abbas Jalalpuri, and Saeed Ahmad Rafiq are examined to highlight diverse perspectives on the origin and function of religion. In contrast, the Islamic viewpoint of religion as a divinely revealed system is presented through the concept of the revelatory theory of religion. The research also offers a systematic critique of evolutionary theories of religion, arguing that such approaches fail to adequately explain the universality, continuity, and moral authority of religious belief. By integrating Qur’anic teachings, classical Islamic scholarship, and contemporary intellectual discourse, this study seeks to present religion as an essential, coherent, and divinely guided framework that governs both the spiritual and material dimensions of human life.